2023
DOI: 10.1177/08919887231195235
|View full text |Cite
|
Sign up to set email alerts
|

Late-Life High Blood Pressure and Enlarged Perivascular Spaces in the Putaminal Regions of Community-Dwelling Japanese Older Persons

Abstract: Background Enlarged perivascular spaces (EPVS) of the brain may be involved in dementia, such as Alzheimer’s disease and cerebral small vessel disease (CSVD). Hypertension has been reported to be a risk factor for dementia and CSVD, but the association between blood pressure (BP) and perivascular spaces is still unclear. The aim of this study was to determine the association between BP and EPVS volumes and to examine the interactions of relevant factors. Methods A total of 9296 community-dwelling subjects aged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Eleven out of thirteen studies identified a positive association between hypertension and PVS burden (Ballerini et al, 2019; Huang, Zhu, et al, 2021b; Wang et al, 2021; Wang, Chappell, et al, 2016; Cheng et al, 2022; Hadad et al, 2022; Charisis et al, 2023; Evans et al, 2023; Tachibana et al, 2024; Zebarth et al, 2023; Duperron et al, 2023). Duperron et al, (2023), the largest study amongst the ones included, found causal associations of high blood pressure with BG and hippocampal PVS, and of BG PVS and hippocampal PVS with stroke, accounting for blood pressure, even after Mendelian randomisation.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven out of thirteen studies identified a positive association between hypertension and PVS burden (Ballerini et al, 2019; Huang, Zhu, et al, 2021b; Wang et al, 2021; Wang, Chappell, et al, 2016; Cheng et al, 2022; Hadad et al, 2022; Charisis et al, 2023; Evans et al, 2023; Tachibana et al, 2024; Zebarth et al, 2023; Duperron et al, 2023). Duperron et al, (2023), the largest study amongst the ones included, found causal associations of high blood pressure with BG and hippocampal PVS, and of BG PVS and hippocampal PVS with stroke, accounting for blood pressure, even after Mendelian randomisation.…”
Section: Resultsmentioning
confidence: 99%